Development of Fuzzy Logic Control System - Lim, Oon Pin; Ling, T. C.; Phang, K. K. (Malaysian Journal of Computer Science, 1998)
Describes the architecture of the fuzzy logic controller (FLC) and its advantages in various industrial applications. A prototype of cooperative neural fuzzy controller, CONEFCON, has been developed to demonstrate the feasibility of FLC.